Protocolo de detección de ametropías en niños de 3 a 5 años (2021)
Bearing in mind that in the report of the comprehensive eye health care program 2016-2022, reported in 2016 by the Colombian Ministry of Health, finds that, in terms of myopia, hyperopia and astigmatism, the defect is more frequent of refraction of hyperopia in women in the range of ages between 5 to the 9 years. Where they were found, a total of 15,292 cases with a prevalence of 0.79% (5). In addition, it highlights that the national government developed a proposal to reduce this condition vision for the year 2022 through the national program of comprehensive care in visual health 2016-2022, which aims to design intervention strategies that allow the identification of possible alterations in vision up to 20%, adjusting to the objectives defined for the year 2016 (5). Additionally, the strategies that are sought to be implemented to reduce these figures are: identify refractive errors at an early age (from birth), in all the areas in which the child is; train all staff including doctors, nurses, pediatricians among others, in visual and ocular aspects, in order to encourage timely referral to a visual health professional (5). This is how this protocol is created in search of helping to detect visual ametropia in preschool children of timely manner.